2014 International Conference on Power System Technology 2014
DOI: 10.1109/powercon.2014.6993873
|View full text |Cite
|
Sign up to set email alerts
|

Small-signal modeling and stability analysis of DC microgrid with multiple type of loads

Abstract: DC microgrid is an efficient solution for integration of multiple Distributed Generations (DGs) and loads. The stability of DC system can be influenced by different kinds of loads. In this paper, the small signal model is established for DC microgrid with multi-type of loads. Lyapunov Stability Theory is applied to investigate the dynamic stability of DC microgrid. Traces of eigenvalues demonstrate that high portion of Constant Power Loads (CPL) may bring negative effect to DC microgrid while Constant Current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Load proportion could significantly affect the small-signal stability performance of the DC MG. Trajectories of eigenvalues suggested that a high portion of constant power load (CPL) could adversely affect the damping of the DC MG due to its negative impedance characteristic [54][55][56][57][58]. Conversely, the constant resistive load (CRL) increases the damping characteristics of the MG. Table 3 summarizes the key technical aspects related to the small-signal stability of the MG.…”
Section: Small-signal Stability In Microgridmentioning
confidence: 99%
“…Load proportion could significantly affect the small-signal stability performance of the DC MG. Trajectories of eigenvalues suggested that a high portion of constant power load (CPL) could adversely affect the damping of the DC MG due to its negative impedance characteristic [54][55][56][57][58]. Conversely, the constant resistive load (CRL) increases the damping characteristics of the MG. Table 3 summarizes the key technical aspects related to the small-signal stability of the MG.…”
Section: Small-signal Stability In Microgridmentioning
confidence: 99%